Deixis, Meta-Perceptive Gaze Practices, and the Interactional Achievement of Joint Attention - Stukenbrock, Anja (Frontiers in Psychology, 2020)
Across languages, deictics have been argued to constitute a particular class of linguistic items. They fulfill one of the most central functions in human communication: the establishment of joint attention. Joint attention is crucial for the development of the social and cognitive skills for "the cooperative infrastructure of human communication" (Tomasello, 2008, 7). Among the manifold resources deployed by participants to direct co-participants' visual attention to phenomena in shared space (demonstratio ad oculos et ad aures, Bühler, 1965 [1934]) deixis and embodied pointing are of paramount importance. While deixis, gestural pointing, and their interpersonal coordination have been investigated by a growing body of research over the past decades, the role of eye gaze has largely been neglected. Based on dual mobile eye-tracking data of naturally occurring social interaction, my paper investigates the function of gaze practices deployed concurrently with deictics and pointing to establish joint attention as a mutually known achievement. Starting from previous work on the coordination of verbal and embodied pointing in face-to-face interaction (Stukenbrock, 2015), it aims to overcome this eye gaze gap in research on deixis. It proposes that gaze constitutes an indispensable resource and integrative part of how joint attention is cooperatively accomplished. Of central concern are moments in which mutuality of perception, and meta-perception, i.e. ego perceiving alter's visual orientation to a phenomenon, are consequential for the change of common ground brought about by joint attention. Although taken for granted, mutuality of perception is an interactional achievement. It is accomplished by spatially calibrated and temporally fine-tuned practices of mutual monitoring that become socially visible and scientifically analyzable at the moment of execution. The analysis focuses on two meta-perceptive practices: gaze following and gaze monitoring. Despite the striking similarity of gaze being directed at gaze in visual meta-perception, practices of observing what others do with their eyes perform different functions. These are context-dependent, positionally sensitive, tied to participant roles, and temporally fine-tuned to the emerging stream of verbal and embodied conduct. Meta-perceptive practices enhance the succesful establishment of joint attention as a mutually known fact and serve to create perceptually grounded moments of intersubjectivity.